Clinical Outcomes and Neuroimaging Profiles in Nondisabled Patients With Anticoagulant-Related Intracerebral Hemorrhage. Issue 10 (October 2018) - Lioutas, Vasileios-Arsenios; Goyal, Nitin; Katsanos, Aristeidis H.; Krogias, Christos; Zand, Ramin; Sharma, Vijay K.; Varelas, Panayiotis; Malhotra, Konark; Paciaroni, Maurizio; Sharaf, Aboubakar; Chang, Jason; Karapanayiotides, Theodore; et al.
Abstract : Background and Purpose—: The aim of this study was to prospectively validate our prior findings of smaller hematoma volume and lesser neurological deficit in nonvitamin K oral anticoagulant (NOAC) compared with Vitamin K antagonist (VKA)-related intracerebral hemorrhage (ICH). Methods—: Prospective 12-month observational study in 15 tertiary stroke centers in the United States, Europe, and Asia. Consecutive patients with premorbid modified Rankin Scale score of <2 with acute nontraumatic anticoagulant-related ICH divided into 2 groups according to the type of anticoagulant: NOAC versus VKA. We recorded baseline ICH volume, significant hematoma expansion (absolute [12.5 mL] or relative [>33%] increase), neurological severity measured by National Institutes of Health Stroke Scale score, 90-day mortality, and functional status (modified Rankin Scale score). Results—: Our cohort comprised 196 patients, 62 NOAC related (mean age, 75.0±11.4 years; 54.8% men) and 134 VKA related (mean age, 72.3±10.5; 73.1% men). There were no differences in vascular comorbidities, antiplatelet, and statin use; NOAC-related ICH patients had lower median baseline hematoma volume (13.8 [2.5–37.6] versus 19.5 [6.6–52.0] mL; P =0.026) and were less likely to have severe neurological deficits (National Institutes of Health Stroke Scale score of >10 points) on admission (37% versus 55.3%, P =0.025). VKA-ICH were more likely to have significant hematoma expansion (37.4% versus 17%, P =0.008). NOAC pretreatment was independently associated with smaller baseline hematoma volume (standardized linear regression coefficient:−0.415 [95% CI, −0.780 to −0.051]) resulting in lower likelihood of severe neurological deficit (odds ratio, 0.44; 95% CI, 0.22−0.85) in multivariable-adjusted models. Conclusions—: Patients with NOAC-related ICH have smaller baseline hematoma volumes and lower odds of severe neurological deficit compared with VKA-related ICH. These findings are important for practicing clinicians making anticoagulation choices. Abstract : Supplemental Digital Content is available in the text.